Construction of nuptiality tables for the hilly rural population of Uttarakhand: 1931-2000 - Pandey, Shubham; Singh, Ankit; Awasthi, Saumya; Kaur, Supreet (International Journal Of Community Medicine And Public Health, 2018)
Background: Nuptiality has a strong association with socio demographic and socio economic change in society. So, it has immense importance to study the female age at marriage in society. In order to study the nuptiality pattern in rural areas of Uttarakhand State, India, a number of measures like crude marriage rate, age sex specific marriage rates and similar other rates are used in the nuptiality tables. Methods: This paper deals with the study on the change in the nuptiality pattern through the life table approach in the seven cohorts 1931-40, 1941-50, 1951-60, 1961-70, 1971-80, 1981-90 and 1991-2000. It is observed that the rates are changing with time. We also calculate expected number of years of single life remaining to a single person at age x. It is also observed that the age at marriage is increasing as the time passes. The data for this has been collected through the primary collection technique and the paper includes all the nuptiality tables for the seven cohort systems. Results: It is observed that the rates are changing with time. No significant time trend has been observed in the nuptiality rates among the single population of hilly rural area of Uttarakhand. From the table we can see that initially, at the age group 10 the rate is small and it increases rapidly till it reaches to maximum at the age group 20. Conclusions: In the field of marriage for the Indian population, it is suggested that development and examination of nuptiality tables over various periods would constitute a distinct progression in the investigation of Indian nuptiality.